HKOH‐1: A Highly Sensitive and Selective Fluorescent Probe for Detecting Endogenous Hydroxyl Radicals in Living Cells. Issue 42 (13th September 2017) - Bai, Xiaoyu; Huang, Yueyang; Lu, Mingyang; Yang, Dan
Abstract: The hydroxyl radical ( . OH), one of the most reactive and deleterious reactive oxygen species (ROS), has been suggested to play an essential role in many physiological and pathological scenarios. However, a reliable and robust method to detect endogenous . OH is currently lacking owing to its extremely high reactivity and short lifetime. Herein we report a fluorescent probe HKOH‐1 with superior in vitro selectivity and sensitivity towards . OH. With this probe, we have calibrated and quantified the scavenging capacities of a wide range of reported . OH scavengers. Furthermore, HKOH‐1r, which was designed for better cellular uptake and retention, has performed robustly in detection of endogenous . OH generation by both confocal imaging and flow cytometry. Furthermore, this probe has been applied to monitor . OH generation in HeLa cells in response to UV light irradiation. Therefore, HKOH‐1 could be used for elucidating . OH related biological functions. Abstract : Highly sensitive and selective probes for hydroxyl radical detection have been developed. The fluorescent probe HKOH‐1 has been applied in the screening of antioxidant capacities of several reported hydroxyl radical scavengers. Endogenous hydroxyl radical generation in multiple cell types has been detected with HKOH‐1r by both confocal imaging and flow cytometry.